UPAYA MEWUJUDKAN KEHARMONISAN RUMAH TANGGA MELALUI PEMBINAAN PRANIKAH DI KANTOR URUSAN AGAMA (STUDI DI KUA KECAMATAN PRAYA TIMUR) - TITIN APRIANI (Universitas Mahasaraswati Mataram, 2020)
The objectives of this research are: (a) to find out how effective methods of premarital coaching are at the PrayaTimur District KUA (Religious Affairs Office), (b) to find out what obstacles are found in Pre-Marriage Coaching for Bride and Groom Candidates in the KUA (Office of Affairs). Religion) PrayaTimur District. This research is useful for providing knowledge, especially for the prospective bride and groom who will carry out the marriage.The result of this research shows that this prenuptial guidance can be carried out by the Head of KUA and Penghulu within the grace period from registration to the implementation of the marriage contract. This time is long enough to be able to convey several things related to domestic life, so that the bride and groom can understand and use them in navigating their domestic life according to religious and statutory expectations. Counting 10 working days before the marriage contract takes place.